Two Case Reports of Neuroinvasive West Nile Virus Infection in the Critical Care Unit - Edgardo M. Flores Anticona; Hadeel Zainah; Daniel R. Ouellette; Laura E. Johnson (Case Reports in Infectious Diseases)
We describe the clinical course of two cases of neuroinvasive West Nile Virus (WNV) infection in the critical care unit. The first case is a 70-year-old man who presented during summer with mental status changes. Cerebrospinal fluid (CSF) analysis revealed pleocytosis with lymphocyte predominance. WNV serology was positive in the CSF. His condition worsened with development of left-sided weakness and deterioration of mental status requiring intensive care. The patient gradually improved and was discharged with residual left-sided weakness and near-complete improvement in his mental status. The second case is an 81-year-old man who presented with mental status changes, fever, lower extremity weakness, and difficulty in walking. CSF analysis showed pleocytosis with neutrophil predominance. WNV serology was also positive in CSF. During the hospital stay his mentation worsened, eventually requiring intubation for airway protection and critical care support. The patient gradually improved and was discharged with residual upper and lower extremity paresis. Neuroinvasive WNV infection can lead to significant morbidity, especially in the elderly. These cases should be suspected in patients with antecedent outdoor activities during summer. It is important for critical care providers to be aware of and maintain a high clinical suspicion of this disease process.